Kesejahteraan Keluarga Berhubungan Dengan Kejadian Kekurangan Energi Kronik Pada Ibu Hamil - widyaningsih, heriyanti; Noor Sholekhah; Biyanti Dwi Winarsih; Noor Faidah; Sri Hartini (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2025)
Pregnancy can trigger Chronic Energy Deficiency (CED). The main factors influencing CED in pregnant women include food intake, family welfare, and nutritional status. Efforts to reduce the prevalence of CED in Indonesia encompass early screening, nutrition education, and the provision of supplementary food. The novelty of this study lies in identifying the relationship between family welfare levels and the incidence of CED in pregnant women. The study aims to describe family welfare levels, examine the incidence of CED, and analyze the relationship between family welfare and CED occurrence. This research utilized an analytical observational approach with a cross-sectional design. The study population consisted of pregnant women in the UPTD Puskesmas Mayong I, Jepara area, in 2022, with inclusion criteria being pregnant women in their second and third trimesters who attended antenatal care at the maternal and child health clinic. The sample size was 87 respondents, calculated using the Slovin formula (error margin 0.05%), and sampling was conducted using non-probability consecutive sampling. Data analysis employed the chi-square test. Most families were categorized as